Nitric Oxide Is Required for L-Type Ca2+ Channel-Dependent Long-Term Potentiation in the Hippocampus - Pigott, Beatrice M.; Garthwaite, John (Frontiers in Synaptic Neuroscience, 2016)
Nitric oxide (NO) has long been implicated in the generation of long-term potentiation (LTP) and other types of synaptic plasticity, a role for which the intimate coupling between NMDA receptors (NMDARs) and the neuronal isoform of NO synthase is likely to be instrumental in many instances. While many types of synaptic plasticity depend on NMDA receptors, others do not, an example of which is LTP triggered by opening of L-type voltage-gated Ca2+ channels (L-VGCCs) in postsynaptic neurons. In CA3-CA1 synapses in the hippocampus, NMDAR-dependent LTP appears to be primarily expressed postsynaptically whereas L-VGCC-dependent LTP, which often coexists with NMDAR-dependent LTP, appears mainly to reflect enhanced presynaptic transmitter release. Since NO is an excellent candidate as a retrograde messenger mediating post-to-presynaptic signaling, we sought to determine if NO functions in L-VGCC-dependent LTP in mouse CA3-CA1 synapses. When elicited by a burst type of stimulation with NMDARs and the associated NO release blocked, L-VGCC-dependent LTP was curtailed by inhibition of NO synthase or of the NO-receptor guanylyl cyclase to the same extent as occurred with inhibition of L-VGCCs. Unlike NMDAR-dependent LTP at these synapses, L-VGCC-dependent LTP was unaffected in mice lacking endothelial NO synthase, implying that the major source of the NO is neuronal. Transient delivery of exogenous NO paired with tetanic synaptic stimulation under conditions of NMDAR blockade resulted in a long-lasting potentiation that was sensitive to inhibition of NO-receptor guanylyl cyclase but was unaffected by inhibition of L-VGCCs. The results indicate that NO, acting through its second messenger cGMP, plays an unexpectedly important role in L-VGCC-dependent, NMDAR-independent LTP, possibly as a retrograde messenger generated in response to opening of postsynaptic L-VGCCs and/or as a signal acting postsynaptically, perhaps to facilitate changes in gene expression.